2023
DOI: 10.1101/2023.03.13.531514
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An O-GlcNAc transferase pathogenic variant that affects pluripotent stem cell self-renewal

Abstract: O-linked β-N-acetylglucosamine (O-GlcNAc) transferase (OGT) is an essential enzyme that modifies proteins with O-GlcNAc. Inborn OGT genetic variants were recently shown to mediate a novel type of Congenital Disorder of Glycosylation (OGT-CDG) which is characterized by X-linked intellectual disability (XLID) and developmental delay. Here, we report an OGTC921Y variant which co-segregates with XLID and epileptic seizures, and results in loss of catalytic activity. Colonies formed by mouse embryonic stem cells ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 92 publications
0
1
0
Order By: Relevance
“…Many mutations in OGT causal in intellectual disability modelled previously do not result in a decrease in global O-GlcNAcylation either in embryonic stem cells or patient derived fibroblasts, in many cases due to feedback mechanisms reducing OGA protein levels 3,5,8 . The mutation modelled here is one of only two which has been shown to reduce global O-GlcNAcylation when modelled in mammalian cells 6,22 . Here, we have shown that patient mutations in the catalytic domain of OGT result in decreased O-GlcNAcylation in adult flies, corroborating previous results 5 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many mutations in OGT causal in intellectual disability modelled previously do not result in a decrease in global O-GlcNAcylation either in embryonic stem cells or patient derived fibroblasts, in many cases due to feedback mechanisms reducing OGA protein levels 3,5,8 . The mutation modelled here is one of only two which has been shown to reduce global O-GlcNAcylation when modelled in mammalian cells 6,22 . Here, we have shown that patient mutations in the catalytic domain of OGT result in decreased O-GlcNAcylation in adult flies, corroborating previous results 5 .…”
Section: Discussionmentioning
confidence: 99%
“…Expanding upon these results, we have demonstrated that an OGT-CDG catalytic domain mutation can reduce O-GlcNAcylation throughout development, despite a compensatory increase in total DmOGT protein. When modelled in mouse embryonic stem cells, this mutation (C921Y in humans and mice) also results in an increase in OGT protein levels 22 . It is tempting to assert that increased OGT, as opposed to decreased OGA, is a homeostatic mechanism linked specifically to this mutation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, several OGT missense mutations have been identified and characterized in patients affected by a new neurodevelopmental disorder associated with intellectual disability, development delay and dysmorphic features, called OGT-linked Congenital Disorder of Glycosylation (OGT-CDG) (18)(19)(20)(21)(22)(23)(24)(25). While this highlighted an important role of O-GlcNAcylation in neurodevelopment, the molecular mechanisms underlying the disease remain unknown.…”
Section: Introductionmentioning
confidence: 99%